Popcorn (Zea mays L. var. everta) yield and yield components as influenced by the timing of broadcast flaming - Ulloa, Santiago M.; Datta, Avishek; Cavalieri, Sidnei D. [UNESP]; Lesnik, Mario; Knezevic, Stevan Z. (Elsevier B.V., 2010)
Farmers are interested in producing popcorn under organic production systems and propane flaming could be a significant component of an integrated weed management program. The objective of this study was to collect baseline information on popcorn tolerance to broadcast flaming as influenced by propane dose and crop growth stage at the time of flaming. Field experiments were conducted at the Haskell Agricultural Laboratory of the University of Nebraska, Concord, NE in 2008 and 2009 using five propane doses (0, 13, 24, 44 and 85 kg ha(-1)) applied at the 2-leaf, 5-leaf and 7-leaf growth stages. Propane was applied using a custom-built research flamer driven at a constant speed of 6.4 km h(-1). Crop response to propane dose was described by log-logistic models on the basis of visual estimates of crop injury, yield components (plants m(-2), ears plant(-1), kernels cob(-1) and 100-kernel weight) and grain yield. Popcorn response to flaming was influenced by the crop growth stage and propane dose. Based on various parameters evaluated, popcorn flamed at the 5-leaf showed the highest tolerance while the 2-leaf was the most susceptible stage. The maximum yield reductions were 45%, 9% and 16% for the 2-leaf, 5-leaf and 7-leaf stages, respectively. In addition, propane doses that resulted in a 5% yield loss were 23 kg ha(-1) for the 2-leaf and 7-leaf and 30 kg ha(-1) for the 5-leaf stage. Flaming has a potential to be used effectively in organic popcorn production if properly used. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dose-response curves; Crop tolerance; Non-chemical weed control; Organic crop production